The Effect of Prey Density on Life Table Parameters of Hippodamia variegata (Coleoptera: Coccinellidae) Fed on Aphis gossypii (Hemiptera: Aphididae) under Laboratory Conditions. (9th July 2013) - Davoodi Dehkordi, Soodeh; Sahragard, Ahad; Hajizadeh, Jalil
Abstract : Life table gives the most comprehensive explanation of the survivorship, development, and reproduction of a population. The life table parameters of ladybeetle, Hippodamia variegata (Coleoptera: Coccinellidae), on different densities (20, 40, 60, 80, and 100) of third instar nymphs of Aphis gossypii were studied in a growth chamber (25 ± 1 °C, 65 ± 5 % RH, and a photoperiod of 16L: 8D h). The adult preovipositional period and the total preovipositional period of female H. variegata were reduced as the prey density increased. The oviposition period was longer when prey density increased. Female longevity also increased significantly with increasing prey density. Fecundity was dependent on prey density. The lowest fecundity was obtained at density of 20 prey (70.7  ±  8.3 ) and the highest at density of 100 (1132.2 ± 57.6 eggs). Intrinsic rate of increase was dependent on prey density and ranged from 0.0788 ± 0.005 to 0.187 ± 0.009  d −1 (female/female/day) with increasing prey density. Net reproductive rate and gross reproductive rate were also increased with increasing prey density. The peak reproductive values were dependent on prey density. However, mean generation time decreased as prey density increased. It was concluded that the increase in the density of A. gossypii nymphs had positive and significant effects on reproductive parameters of H. variegata .